Hybrid inorganic-organic proton-conducting membranes based on SPEEK doped with WO3 nanoparticles for application in vanadium redox flow batteries. (20th June 2019) - Sun, Chuanyu; Negro, Enrico; Vezzù, Keti; Pagot, Gioele; Cavinato, Gianni; Nale, Angeloclaudio; Herve Bang, Yannick; Di Noto, Vito
Abstract: The development of innovative proton-conducting membranes exhibiting an improved [H + /VO 2+ ] ion selectivity in comparison with baseline perfluorinated ionomers ( e.g., Nafion) is critical to prompt the large-scale implementation of vanadium redox flow batteries (VRFBs) characterized by a performance and cyclability compatible with the applications. This paper pursues this objective by reporting the preparation and characterization of a new family of hybrid inorganic-organic membranes, that are labeled "[SPEEK/(WO 3 ) x ]", consisting of a sulfonated poly (ether ether ketone) (SPEEK) matrix hosting between 0 and 23.6 wt% of WO3 nanoparticles (NPs). The physicochemical characterization of the [SPEEK/(WO3 )x ] membranes elucidates the impact of the introduction of WO3 NPs on the thermal, structural and transport properties of the SPEEK host. It is found that the [SPEEK/(WO3 )0.20 ] membrane presents the highest [H + /VO 2+ ] ion selectivity (2.1 × 10 4 S min cm −3 ), that is more than three times higher than that of recast Nafion (6.5 × 10 3 S min cm −3 ). [SPEEK/(WO3 )0.20 ] is then mounted in a single cell VRFB, that is tested extensively under realistic operating conditions and demonstrates a coulombic efficiency and cyclabilty that are improved with respect to the corresponding figures of a VRFB incorporating a Nafion 212 membrane to provide the basis for a comparison. This outcome is in compliance with the result of the "ex-situ" investigations, and allows for the proposal of a structural model correlating the physicochemical properties of the [SPEEK/(WO3 )x ] membranes with the transport properties and the proton conductivity. Highlights: Hybrid [SPEEK/(WO3 )x ] membranes are prepared and investigated for application in VRFBs. The transport properties of the [SPEEK/(WO3 )x ] membranes are strongly influenced by x. At 30 °C the [H + /VO 2+ ] ion selectivity of [SPEEK/(WO3 )0.20 ] is 3.2 times higher than that of Nafion 212. The VRFB mounting [SPEEK/(WO3 )0.20 ] shows a lower capacity fade than that mounting Nafion 212.